Agricultural soils potentially contaminated: risk assessment procedure case studies - Eleonora Beccaloni; Fabiana Vanni; Silvana Giovannangeli; Massimiliano Beccaloni; Mario Carere (Istituto Superiore di Sanità, 2010)
At the moment, the health-environmental risk analysis is used to decision-making targets in the contaminated sites management; this procedure allows to assess the quantitative health risk related to the pollutants presence in environmental compartments, as soil and waters. As regards potentially contaminated agricultural soils, the ingestion of food from vegetable and/or animal source, produced inside the contaminated area, is the most suitable way to assess the health risk. As an official procedure to this assessment is not available, the National Institute for Health (Istituto Superiore di Sanità, ISS) has worked out an operating procedure, organized into several phases, depending on the available specific-site know-how. In this document, agricultural soils potentially contaminated in two sites have been studied; the sites are the following: Brescia Caffaro and Torviscosa.